Handbook of pumps and pumping - Nesbitt, Brian
Written by an experienced engineer, this book contains practical information on all aspects of pumps including classifications, materials, seals, installation, commissioning and maintenance. In addition you will find essential information on units, manufacturers and suppliers worldwide, providing a unique reference for your desk, R & D lab, maintenance shop or library. * Includes maintenance techniques, helping you get the optimal performance out of your pump and reducing maintenance costs * Will help you to understand seals, couplings and ancillary equipment, ensuring systems are set up properly to save time and money * Provides useful contacts for manufacturers and suppliers who specialise in pumps, pumping and ancillary equipment.